IMPLEMENTATION AND TOURIST PERCEPTION OF SAPTA PESONA AT TAMAN KUPU-KUPU, SUKAJADI TOURISM VILLAGE, BOGOR - Riani P. Ishak (Universitas Terbuka, 2021)
This study aims to determine, describe, and analyze (1) the implementation of Sapta Pesona at Taman Kupu-Kupu in the Sukajadi Tourism Village and (2) the tourists' perception of Sapta Pesona actualization at Taman Kupu-Kupu in the Sukajadi Tourism Village. The research method used in this research is descriptive research with a mixed approach. Data collection techniques used are observation, interviews, questionnaires, and documentation and literacy. The analysis method used is (1) Miles and Huberman qualitative data analysis in the form of data reduction, data presentation, and drawing conclusions. Then the second is quantitative data analysis with descriptive statistical analysis using SPSS. The sample in this study were tourists who visited the Taman Kupu-Kupu in Sukajadi Tourism Village in May 2021, which is limited due to pandemic Covid-19. The results of this study indicate that (1) the application of Sapta Pesona Taman Kupu-Kupu Sukajadi Tourism Village on the seven elements has generally been carried out well, however, each indicator still can be improved to the most optimal level, in particular for elements safe, clean, cool, and beautiful. Furthermore, a survey on tourist perceptions in regard to the implementation of Sapta Pesona at Taman Kupu-Kupu Sukajadi Tourism Village is rated excellent on these elements: orderliness, friendliness, and memorable. Various efforts can still be worked on to reach maximum value for Sapta Pesona implementation. By improving its organizational strategy, providing skills training for its employee, preparing written and displayed Standard Operating Procedure in the park, building cooperation with related parties and improving marketing and promotion strategy are some recommendations can be conducted by the management of Taman Kupu-Kupu Sukajadi Tourism. Based on the results of this study. Moreover, it is strongly recommended that the Bogor Regency Tourism and Culture Office should pay more attention to conducting regular supervision of developing tourism villages in Bogor so that the implementation of Sapta Pesona can be optimized. Keywords: Sapta Pesona, Tourist Perception, Tourism Village , Sukajadi Village